Duhuo Jisheng Decoction suppresses apoptosis and mitochondrial dysfunction in human nucleus pulposus cells by miR-494/SIRT3/mitophagy signal axis - Wei Liu; Xiaolong Zhao; Xuejian Wu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Increasing evidence suggests that mitophagy is responsible for the pathogenesis of intervertebral disk (IVD) degeneration. Previous studies have shown that Duhuo Jisheng Decoction (DHJSD), a classic Fangji of traditional Chinese medicine, can delay IVD degeneration; however, its specific mechanism of action is unknown. In this study, we investigated the mechanism by which DHJSD treatment prevented IVD degeneration in IL-1β-treated human nucleus pulposus (NP) cells in vitro. Methods Cell Counting Kit-8 was performed to explore the effects of DHJSD on the viability of NP cells exposed to IL-1β. The mechanism by which DHJSD delays IVD degeneration was explored using luciferase reporter assay, RT-qPCR, western blotting, TUNEL assay, mitophagy detection assay, Mito-SOX, Mitotracker and in situ hybridization. Results We observed that DHJSD enhanced the viability of NP cells treated with IL-1β in a concentration-time dependent approach. Moreover, DHJSD lessened IL-1β-induced NP apoptosis and mitochondrial dysfunction and activated mitophagy in NP cells treated with IL-1β. Mitophagy suppressor cyclosporin A reversed the beneficial impacts of DHJSD in NP cells. In addition, the differential expression of miR-494 regulated IL-1β-induced NP apoptosis and mitochondrial dysfunction, and the protective impact of miR-494 on NP cells treated with IL-1β was achieved by mitophagy activation, which was regulated by its target gene, sirtuin 3 (SIRT3). Finally, we observed that DHJSD treatment could effectively delay IL-1β-induced NP apoptosis by affecting the miR-494/SIRT3/mitophagy signal axis. Conclusions These results show that the miR-494/SIRT3/mitophagy signaling pathway is responsible for the apoptosis and mitochondrial dysfunction of NP cells and that DHJSD may exert protective effects against IVD degeneration by regulating the miR-494/SIRT3/mitophagy signal axis.